Remainder

Algebra Level 3

If the polynomial P ( x ) = x 9 x 6 + x 3 1 P(x)={ x }^{ 9 }-{ x }^{ 6 }+{ x }^{ 3 }-1 leaves r ( x ) r(x) as remainder when divided by d ( x ) = x 2 + x + 1 d(x)={ x }^{ 2 }+x+1 , then, evaluate r ( 2015 ) r(2015) .


Inspiration: Preparatory Classes to the Technological Institute of Aeronautics (ITA - Brazil).


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Jaydee Lucero
Oct 15, 2015

Write P ( x ) P(x) as P ( x ) = x 9 x 6 + x 3 1 = ( x 3 1 ) ( x 6 + 1 ) = ( x 1 ) ( x 2 + x + 1 ) ( x 6 + 1 ) P(x)=x^9 - x^6 + x^3 - 1 = (x^3 - 1)(x^6 + 1) = (x - 1)(x^2 + x + 1)(x^6 + 1) So, P P is divisible by d ( x ) = x 2 + x + 1 d(x) = x^2 + x + 1 , and therefore r ( x ) = 0 r(x) = 0 . Thus r ( 2015 ) = 0 r(2015) = \boxed{0} .

Lu Chee Ket
Oct 24, 2015

I divided straight away and found that x^9 - x^6 + x^3 - 1 = (x^2 + x + 1)(x^7 - x^6 + x - 1);

The remainder is a constant 0;

Therefore, r (2015) = 0.

x 3 1 = ( x 1 ) ( x 2 + x + 1 ) x^{ 3 }-1=(x-1)({ x }^{ 2 }+x+1) . Thus, x 3 1 x^{ 3 }-1 leaves 0 0 as remainder in the division by ( x 2 + x + 1 ) ({ x }^{ 2 }+x+1)

Hence:

x 3 1 0 ( m o d x 2 + x + 1 ) x 3 1 ( m o d x 2 + x + 1 ) x^{ 3 }-1\equiv 0(mod\quad { x }^{ 2 }+x+1)\quad \Longleftrightarrow \quad x^{ 3 }\equiv 1(mod\quad { x }^{ 2 }+x+1)

So, by the properties of Modular Arithmetics:

( x 3 ) 3 ( 1 ) 3 ( m o d x 2 + x + 1 ) x 9 1 ( m o d x 2 + x + 1 ) ( x 3 ) 2 ( 1 ) 2 ( m o d x 2 + x + 1 ) x 6 1 ( m o d x 2 + x + 1 ) x 3 1 ( m o d x 2 + x + 1 ) 1 1 ( m o d x 2 + x + 1 ) { ({ x }^{ 3 }) }^{ 3 }\equiv { (1) }^{ 3 }(mod\quad { x }^{ 2 }+x+1)\quad \Longleftrightarrow \quad x^{ 9 }\equiv 1(mod\quad { x }^{ 2 }+x+1)\quad \\ { -({ x }^{ 3 }) }^{ 2 }\equiv -{ (1) }^{ 2 }(mod\quad { x }^{ 2 }+x+1)\quad \Longleftrightarrow \quad -x^{ 6 }\equiv -1(mod\quad { x }^{ 2 }+x+1)\\ x^{ 3 }\equiv 1(mod\quad { x }^{ 2 }+x+1)\\ -1\equiv -1(mod\quad { x }^{ 2 }+x+1)

Summing it up, we get:

x 9 x 6 + x 3 1 1 1 + 1 1 ( m o d x 2 + x + 1 ) p ( x ) 0 ( m o d x 2 + x + 1 ) { x }^{ 9 }-{ x }^{ 6 }+{ x }^{ 3 }-1\equiv 1-1+1-1(mod\quad { x }^{ 2 }+{ x }+1)\Longleftrightarrow \boxed { p(x)\equiv 0(mod\quad { x }^{ 2 }+x+1) }

So r ( x ) = 0 r(x)=0 and then r ( 2015 ) = 0 \boxed { r(2015)=0 }

Moderator note:

I disagree with "Remainder-factor theorem is not helping". You just need to know how to deal with the quadratic case (or any higher degree polynomial).

Atul Shivam
Oct 16, 2015

x 9 x 6 + x 3 1 = ( x 2 + x + 1 ) ( x 7 x 6 + x 1 ) + 0 x^9-x^6+x^3-1=(x^2+x+1)(x^7-x^6+x-1)+0 so the answer is [0]

I think problem is a bit overrated

Siva Meesala
Oct 15, 2015

Given polynomial is divisible by the given divisor.so remainder is 0.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...